Paciente de 5 años de edad con diabetes tipo 1 - Vera Zúñiga, Edwin Leonardo (2022)
Type 1 diabetes mellitus is an autoimmune disease, in which the insulin-producing cells are attacked and destroyed: the beta cells of the pancreas. Lacking insulin, the metabolism of carbohydrates, fats and proteins cannot be carried out correctly. Diabetes mellitus (DM) is characterized by chronic hyperglycemia and its fundamental cause in children is insulin deficiency in the context of autoimmune-type DM. Its proper treatment and monitoring can prevent or delay the onset of complications. It is a lifelong (chronic) disease in which there is a high level of sugar (glucose) in the blood. Type 1 diabetes can occur at any age. It is most often diagnosed in children, adolescents, or young adults. Various factors can contribute to type 1 diabetes, including genetics and certain viruses. Although type 1 diabetes usually appears during childhood or adolescence, it can also begin in adulthood. Despite intense research, type 1 diabetes has no cure.